Extraction and Characterization of Bamboo Shoot Shell Fibers by Sodium Percarbonate Assisted Degumming. Issue 15 (23rd November 2022) - Yang, Yinzhi; Liu, Yuqing; Fang, Yuxi; Teng, Yanfei; Fang, Kaiyang; Xie, Jinpeng; Cao, Xinwang; Deng, Zhongmin
ABSTRACT: The bamboo shoot shell fibers were extracted by using environmental protection oxidant sodium percarbonate combined with alkali oxygen bath method. To explore the influence of various factors on its degumming, the efficiency of degumming through single-factor and orthogonal experiments was assessed. The results showed that the used method had a good effect on the degumming of bamboo shoot shell fiber, and most of the non-cellulose components such as hemicellulose, lignin, and pectin had been removed. After the treatment, the cellulose content and crystallinity were 73.19% and 61.40%, respectively. Taking the degumming rate as the index, the factors such as dosage of sodium percarbonate and hydrogen peroxide, soaking temperature, and time in alkali boiling treatment were optimized. The results showed that the degumming rate was 69.17% when the scouring temperature was 90°C, the alkali boiling time was 120 min, the dosage of sodium percarbonate was 24 g/L, and the dosage of hydrogen peroxide was 40 mL/L. The structure and properties of bamboo shoot shell fiber were analyzed by scanning electron microscope (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analyzer (TGA). The prepared bamboo shoot shell fibers would be considered as a promising and sustainable raw material for the textile industry and other prospects in the future.